Tokoh Filsafat Kontemporer Theodor Adorno - Afiva Indryansa; Zalika Dwi Ayunda; Siti Aminah Putri; Mardhiah Abbas (Getpress Management Journals, 2025)
This article examinea the thought of Theodor W. Adorno as a central figure of the frankfrut school in the development of critical theory. The study focuses on Adorno’s critique of instrumental rationality, the concept of negative dialectics, and the notion of the culture industry as a from of domination within modern capitalism. Employing a qualitative approach with a philosophical-analytical method, this research analyzes Adorno’s major work such as Dialectic of Enlightenment, Negative Dialectics, and his writing on the culture industry. The findings indicate that Adorno views modernity not merely as progress, but as a paradox get generates new forms of domination through distorted rationality. The concept of thr culture industry revelas how mass culture functions aa a mechanism of social control by producing false consciousness and weakening critical awarness. Adorno’s ideas remain highly relevant in contemporary contexts, particularly in addressing issues of digitalization, environmental crisis, and cultural homogenization. Therefore, Adorno’s critical theory offers an important reflective framework for fostering critical consciousness and human emancipation amid global capitalist domination.